Impact of pharmacists as immunizers on influenza vaccination coverage in the community-setting in Nova Scotia, Canada: 2013-2015. Issue 1 (December 2016) - Isenor, Jennifer; Killen, Jessica; Billard, Beverly; McNeil, Shelly; MacDougall, Donna; Halperin, Beth; Slayter, Kathryn; Bowles, Susan
Abstract Background Annual immunization is the most effective way to prevent influenza and its associated complications. However, optimal immunization rates are not being met in Nova Scotia, Canada. Additional providers, such as pharmacists, may improve access and convenience to receive vaccines. Pharmacists began immunizing patients 5 years of age and older within the publicly funded universal influenza vaccination program during the 2013-2014 influenza season. The objective of this study was to evaluate influenza immunization coverage rates before and after pharmacists in Nova Scotia gained authority to immunize as part of the publicly funded universal influenza vaccination program. Methods Influenza immunization data was obtained from the Department of Health and Wellness from 2010 to 2015. Data included billing data from physicians and pharmacists, and local public health data. Vaccination coverage was calculated as proportion of vaccinations received in comparison to the total population. Results Prior to pharmacists immunizing, overall vaccination coverage for Nova Scotia residents 6 months of age and older was 35.8 % in 2012-2013, increasing to 41.8 % coverage in 2013-2014 the year pharmacists began immunizing. A decrease of 1.9 to 39.9 % was observed in 2014-2015. In patients 65 years of age and older living in the community, coverage has increased from 61.8 % in 2012-2013 to 71.6 % in 2013-2014, and again to 73.3 % in 2014-2015 with the addition of pharmacists immunizing. Prior to pharmacists immunizing the highest coverage noted for this portion of the population was 61.8 %. Conclusions The addition of pharmacists as immunizers within a publicly funded universal influenza vaccination program was found to increase overall vaccination coverage in the first year and to maintain higher coverage rates in the second year than those observed before pharmacists began immunizing. Increases in coverage in both years were observed in the elderly. Future research will be required to determine the ongoing impact of the addition of pharmacists as immunizers and other strategies to improve vaccination coverage.